Coady, Amanda. Tom Coady Sailboat, "Mandy Sue" Boat - Heritage NL (1982)
Amanda Coady provided a picture of Tom Coady's sailboat "Mandy Sue" floating in Cape Broyle Harbour. The sails for Mandy Sue were made in town. The community of Cape Broyle is pictured in the background.